2006
DOI: 10.1159/000092116
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Influences on Benzodiazepine Consumption in an Irish Region

Abstract: Misuse of prescription sedatives is a significant problem for addiction treatment services. The aim of this study was to examine the prescribing of diazepam in disadvantaged Irish communities, and to identify factors which may predict diazepam consumption in that population. We examined prescribing trends for those aged 16–69 years in 2002 in a region of the state-funded General Medical Services Scheme. Material deprivation was based on the 2002 Small Area Health Research Unit (SAHRU) deprivation index. The av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…A majority of previous studies investigating long-term use of benzodiazepines have been based on relatively small sample sizes and/or self-reported data (Anthierens et al, 2007;Demyttenaere et al, 2008;Fassaert et al, 2007;Manthey et al, 2012;Manthey et al, 2011;Quigley et al, 2006;Zandstra et al, 2002). The present study contributes to the body of knowledge as it is based on data from a large primary health care population of 919 941 individuals.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…A majority of previous studies investigating long-term use of benzodiazepines have been based on relatively small sample sizes and/or self-reported data (Anthierens et al, 2007;Demyttenaere et al, 2008;Fassaert et al, 2007;Manthey et al, 2012;Manthey et al, 2011;Quigley et al, 2006;Zandstra et al, 2002). The present study contributes to the body of knowledge as it is based on data from a large primary health care population of 919 941 individuals.…”
Section: Introductionmentioning
confidence: 80%
“…In addition, the primary health care centres were located in urban and rural areas as well as in both the Southern and Northern parts of Stockholm The following covariates were included in the model: age, gender, country of origin, income, education, social welfare and marital status. These covariates were included because previous research has shown that sociodemographic factors are related to psychiatric disorders (Andersen and Frydenberg, 2011;Bayard-Burfield et al, 2001;Demyttenaere et al, 2008;Fang et al, 2009;Hjern, 2001;Quigley et al, 2006;Sonnenberg et al, 2012). Age was divided into five categories: 25-44, 45-64, 65-74, and 85+ years.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 Clearly, many doctors unsure of the risk for dependency chose oxazepam rather than diazepam for these patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%